THE EFFECT OF THE ACEH REVENUE AND EXPENDITURE BUDGET, UNEMPLOYMENT AND INFLATION ON POVERTY IN ACEH PROVINCE - Fadillah, Ade; Shafira, Aida; Dayan, Muhammad (J-ISCAN: Journal of Islamic Accounting Research, 2023)
Poverty is a problem for the country and for regions in Indonesia, including the province of Aceh. It is also known from the news that Aceh is a poor area on the island of Sumatra. The government is trying to reduce the percentage of poverty by pursuing development through government programs using the Aceh Revenue and Expenditure Budget. In addition, the unemployment rate of the community also has an impact on poverty because they have no income. Likewise with inflation, if there is an increase, it will have an impact on decreasing people's purchasing power and can be a cause of poverty. This research was conducted with the aim of knowing the effect of APBD, unemployment and inflation on poverty in Aceh Province. The data used are secondary data in the form of APBD, unemployment and inflation and poverty for 2006-2020 obtained from the Directorate General of Fiscal Balance, Ministry of Finance and the Central Statistics Agency for Aceh. Data analysis used multiple linear regression, t test and F test and the coefficient of determination (R2) test. The results showed that the Regional Revenue and Expenditure Budget had a negative and significant effect on poverty. Unemployment and inflation have a positive and insignificant effect on poverty. As much as 88.8% of the Regional Revenue and Expenditure Budget, unemployment and inflation can explain the poverty variable in Aceh Province.